Desempenho da co-digestão anaeróbia de dejetos suínos com inclusão de glicerina bruta - Schwingel, Alice Watte [UNESP]; Orrico, Ana Carolina Amorim; Orrico, Marco Antonio Previdelli; Sunada, Natalia Da Silva; Centurion, Stanley Ribeiro (Universidade Federal do Ceará, 2016)
The aim of this study was to evaluate the performance of the anaerobic co-digestion of pig manure associated with increasing doses of crude glycerine, adopting different periods of hydraulic retention time (HRT). A completely randomised design was used in a 3 x 4 factorial scheme, three HRT (10, 17 and 24 days) and four doses of crude glycerine (0, 5, 10 and 15% of the total solids), with four replications per treatment. The parameters to be evaluated were biogas production and potential production, reduction in total solids (TS), neutral detergent fibre (NDF) and acid detergent fibre (ADF). Biogas production and potential production displayed a quadratic effect for an HRT of 17 and 24 days, showing the doses of 4.09% and 5.63% crude glycerine to be respectively optimal for production, and 4.52% and 5.42% crude glycerine for production potential. There was no difference between the doses of crude glycerine at the HRT of 10 days for reductions in TS. However, a difference was seen between doses at HRT 17 and 24, with the greatest reduction of 54.9% being found when including 5% of crude glycerine at the greatest HRT. The reductions in NDF and ADF were greater with the addition of crude glycerine for an HRT of 10 and 17 days. The inclusion of 4% - 6% crude glycerine at HRT 24 was more efficient in the production of biogas and reducing TS and NDF. With a view to a greater reduction in ADF, higher doses of glycerine can be used in the co-digestion of pig manure.

O objetivo foi avaliar o desempenho da co-digestão anaeróbia de dejetos de suínos associados com crescentes doses de glicerina bruta, adotando-se diferentes tempos de retenção hidráulica (TRH). O delineamento utilizado foi inteiramente casualizado em esquema fatorial 3x4, três TRH (10; 17 e 24 dias) e quatro doses de glicerina bruta (0; 5; 10 e 15% dos sólidos totais), com quatro repetições por tratamento. Os parâmetros avaliados foram produção e potencial de produção de biogás, reduções de sólidos totais (ST), fibra em detergente neutro (FDN) e fibra em detergente ácido (FDA). A produção de biogás e potencial de produção apresentaram efeito quadrático nos TRH de 17 e 24 dias, evidenciando como doses ideais 4,09 e 5,63% de glicerina bruta, respectivamente, para produção e 4,52 e 5,42% de glicerina bruta para potencial de produção. Não houve diferença entre as doses de glicerina bruta dentro do TRH de 10 dias para as reduções de ST. No entanto, foi observado diferença entre as doses nos TRH 17 e 24, com a maior redução observada de 54,9% ao incluir 5% de glicerina bruta no maior TRH. As reduções de FDN e FDA aumentaram de acordo com a adição de glicerina bruta nos TRHs de 10 e 17 dias. A inclusão de 4 a 6% de glicerina bruta no TRH 24 mostrou-se mais eficiente na produção de biogás e reduções de ST e FDN. Já visando maior redução de FDA pode-se utilizar doses mais altas de glicerina a partir da co-digestão com dejetos suínos.
Performance of the anaerobic co-digestion of pig manure with the inclusion of crude glycerine
Keywords: Biodiesel; Waste; Pig farming; Hydraulic retention time; Biodiesel; Resíduos; Suinocultura; Tempo de retenção hidráulica